2008
DOI: 10.1007/s11242-008-9281-1
|View full text |Cite
|
Sign up to set email alerts
|

Robust Multi-D Transport Schemes with Reduced Grid Orientation Effects

Abstract: In this paper we investigate truly multi-D upwind schemes for simulating adverse mobility ratio displacements in porous media. Due to an underlying physical instability at the simulation scale, numerical results are highly sensitive to discretization errors and hence the orientation of the underlying computational grid. We use modified equations analysis to predict preferred flow angles on structured grids for several popular methods and present a conservative, multi-D framework for designing positive upwind s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 24 publications
(31 reference statements)
0
24
0
Order By: Relevance
“…For compositional problems, equation of state and phase equilibrium calculations tend to be the most computationally costly part of the simulation, making the additional cost of the multi-D stencil calculation more tractable by comparison. This work along with our previous work [25] suggests that multi-D upstream weighting methods could prove very valuable for these problems. Finally, the volume relaxed framework presented in Section 3 makes no assumption of the dimensionality of the domain and therefore is equally applicable to 3-D problems.…”
Section: Partially Miscible Modelmentioning
confidence: 56%
See 4 more Smart Citations
“…For compositional problems, equation of state and phase equilibrium calculations tend to be the most computationally costly part of the simulation, making the additional cost of the multi-D stencil calculation more tractable by comparison. This work along with our previous work [25] suggests that multi-D upstream weighting methods could prove very valuable for these problems. Finally, the volume relaxed framework presented in Section 3 makes no assumption of the dimensionality of the domain and therefore is equally applicable to 3-D problems.…”
Section: Partially Miscible Modelmentioning
confidence: 56%
“…In Kozdon et al [25], they were shown to be equivalent (for constant scalar advection) to SPU, the narrow scheme [33], and Koren's scheme [23], respectively. Other schemes are possible within this framework.…”
Section: Definition Of Select Interaction Region Based Schemesmentioning
confidence: 99%
See 3 more Smart Citations